Pelanggaran Batas Wilayah Laut Zona Ekonomi Eksklusif Oleh Nelayan Vietnam Dan Implikasi Hukumnya - Nur Aprilia Al Rasyid; Josina Augustina Yvonne Wattimena; Lucia Charlota Octavina Tahamata (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The South China Sea serves as the maritime boundary between Indonesia and Vietnam. Various issues that have arisen, especially in the Exclusive Economic Zone between Indonesia and Vietnam, are still unresolved to this day. In the last two years of 2021-2022, many foreign fishing vessels of Vietnamese fishermen have carried out illegal fishing activities in North Natuna Waters, where foreign fishing vessels of Vietnamese fishermen carry out fishing using pair trawling fishing methods which can damage fish resources. This resulted in Vietnamese fishermen violating Article 56 of UNCLOS 1982 concerning